Nonspecificity of Chronic Soft Tissue Pain Syndromes - Eldon Tunks (Pain Research and Management)
Persistent (or chronic) pain occurs with a prevalence of about 10% in the adult population, and chronic soft tissue pain is especially problematic. Criteria for diagnosis of these soft tissue pain disorders appear to suffer from specificity problems, even though they appear to be sensitive in distinguishing normal from soft tissue pain sufferers. A few decades ago the term 'neuraesthenia' was used as a diagnosis in individuals who now would probably be diagnosed as suffering from fibromyalgia, chronic fatigue and anxiety disorders with fatigue. Soft tissue pain provokes skepticism, especially among third-party payers, and controversy among clinicians. Recent epidemiological studies have demonstrated sex differences in the prevalence of widespread pain and multiple tender points, which are distributed variably throughout the adult population and tend to be correlated with subjective symptoms. Although there is a tendency for these syndromes to persist, follow-up studies show that they tend to vary in extent and sometimes show remissions over longer follow-up, casting doubt about the distinctions between chronic diffuse pains and localized chronic soft tissue pains. Because both accidents and soft tissue pains are relatively prevalent problems, the possibility of chance coincidence of accident and chronic soft tissue pain in an individual creates the need to be cautious in attributing these syndromes to specific accidents in medicolegal situations. At the same time, the available evidence does not support a generally dismissive attitude towards these patients.